Hitler's Brudervolk : the Dutch and the colonization of occupied Eastern Europe, 1939 - 1945 - Frijtag Drabbe Künzel, Geraldien von 1965- (Routledge studies in modern European history, 2015)
"This is the first academic book on Dutch colonial aspirations and initiatives during WWII. Between the summers of 1941 and 1944, some 5,500 Dutch men and women left their occupied homeland to find employment in the so-called German Occupied Eastern Territories: Belarus, the Baltic countries and parts of Ukraine. This was the area designated for colonization by Germanic people. It was also the stage of the 'Holocaust by Bullets,' a centrally coordinated policy of exploitation and oppression and a ruthless anti-partisan war. This book seeks to answer why the Dutch decided to go there, how their recruitment, transfer and stay were organized, and how they reacted to this scene of genocidal violence. It is a close-up study of racial monomania, of empire-building on the old continent and of collaboration in Nazi-occupied Europe"--